The Impact of Readiness Changes Individual Behavior In The Readiness Process Of Organizational Change After The Deal Acquisition Is Implemented - Budi Alamsyah Siregar; Heru Kurnianto Tjahjono; Achmad Sobirin; Arief Hartono (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study aims to find out how changes in individual behavior have an impact on the process of organizational change to create a synergistic relationship between the main company and the group after the deal acquisition is implemented. This research is an explanatory research, using qualitative case studies as an analysis techniques. This research was conducted by in-depth interviews to obtain data. This study found that individual behavior has a significant impact on creating a synergy relationship between the parent company and the group in the process of organizational change after the acquisition is completed.